2019
DOI: 10.1002/lary.28325
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in children with down syndrome and mild obstructive sleep apnea treated non‐surgically

Abstract: Objectives Nasal steroids, oral anti‐leukotrienes and supplemental oxygen are effective in the treatment of mild obstructive sleep apnea (OSA) in otherwise healthy children. However, their efficacy is unknown in children with Down syndrome (DS). Here we examine the effect of single medication therapy versus observation versus oxygen on polysomnographic outcomes in these children. Methods We reviewed children (<18 years) diagnosed with DS and mild OSA (obstructive apnea‐hypopnea index [oAHI] ≥1 to <5 events/hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…Our results revealed no significant differences in other parameters such as sex, anthropometric measures, comorbidities, and PSG features between symptomatic and asymptomatic patients. Similarly, Howard et al reported no association between reported symptoms and the degree of AHI [ 11 ]. We found that 37% of children with OSA had no symptoms related to sleep abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results revealed no significant differences in other parameters such as sex, anthropometric measures, comorbidities, and PSG features between symptomatic and asymptomatic patients. Similarly, Howard et al reported no association between reported symptoms and the degree of AHI [ 11 ]. We found that 37% of children with OSA had no symptoms related to sleep abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…There are many underlying predisposing factors for OSA in DS such as midfacial hypoplasia, relative macroglossia, glossoptosis, pharyngeal hypotonia, tonsillar hypertrophy, laryngomalacia, and obesity [ 8 10 ]. Additionally, many other comorbid conditions contribute to the occurrence of OSA in DS, including obesity, hypothyroidism, and gastroesophageal reflux (GERD) [ 11 13 ]. Untreated OSA has been associated with significant morbidities in children with DS, including IQ loss [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the medication arm, the baseline AHI was 3.5 compared to 3.6 on subsequent PSG (p = 0.21). They found that in the observation group, the baseline AHI was 2.9 compared to 3.6 on follow-up PSG (p = 0.60) [36]. At follow up, three patients in the medication group reported an improvement in nocturnal symptoms, four reported no change, and one reported worsening of symptoms.…”
Section: Pharmacologic Interventionsmentioning
confidence: 97%
“…For pediatric patients with mild OSA or residual disease status post-AT, pharmacological interventions have been used. These include options such as intranasal corticosteroids and oral leukotriene inhibitors to reduce airway inflammation [36].…”
Section: Pharmacologic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation